Taekwondo Fighting in Training Does Not Simulate the Affective and Cognitive Demands of Competition: Implications for Behavior and Transfer - Maloney, Michael A.; Renshaw, Ian; Headrick, Jonathon; Martin, David T.; Farrow, Damian (Frontiers in Psychology, 2018)
Enhancing practice design is critical to facilitate transfer of learning. Considerable research has focused on the role of perceptual information in practice simulation, yet has neglected how affect and cognition are shaped by practice environments and whether this influences the fidelity of behaviour (Headrick et al., 2015). This study filled this gap by examining the fidelity of individual (cognition, affect, and actions) and interpersonal behaviour of 10 highly-skilled Australian Taekwondo athletes fighting in training compared to competition. Interpersonal behaviour was assessed by tracking location coordinates to analyse distance-time coordination tendencies of the fighter-fighter system. Individual actions were assessed through notational analysis and approximate entropy calculations of coordinate data to quantify the (un)predictability of movement displacement. Affect and cognition were assessed with mixed-methods that included perceptual scales measuring anxiety, arousal and mental effort, and post-fight video-facilitated confrontational interviews to explore how affect and cognitions might differ. Quantitative differences were assessed with mixed models and dependent t-tests. Results reveal that individual and interpersonal behaviour differed between training and competition. In training, individuals attacked less (d=0.81, p<0.05), initiated attacks from further away (d=-0.20, p<0.05) and displayed more predictable movement trajectories (d=0.84, p<0.05). In training, fighters had lower anxiety (d=-1.26, p<0.05), arousal (d=-1.07, p<0.05) and mental effort (d=-0.77, p<0.05). These results were accompanied by changes in interpersonal behaviour, with larger interpersonal distances generated by the fighter-fighter system in training (d=0.80, p<0.05). Qualitative data revealed the emergence of cognitions and affect specific to the training environment, such as reductions in pressure, arousal and mental challenge. Findings highlight the specificity of performer-environment interactions. Fighting in training affords reduced affective and cognitive demands and leads to behaviour of lower fidelity compared to competition. In addition to sampling information, representative practice needs to consider modelling the cognitions and affect of competition to enhance transfer.